Improving Senescent Wound Healing With Local and Systemic Therapies. Issue 1 (July 2018) - Szpalski, Caroline; Butala, Parag; Vandegrift, Meredith T.; Knobel, Denis; Allen, Robert J.; Saadeh, Pierre B.; Warren, Stephen M.
Abstract : Abstract: The population is aging, and the prevalence of chronic wounds is increasing. Because neovascularization is essential for tissue repair and both local and systemic factors affect new blood vessel formation, we hypothesize that altering either pathway would reciprocally enhance wound healing in the aged. To test this hypothesis, p53 was locally suppressed and endothelial progenitor cells (EPCs) were systemically mobilized in a murine model of senescent wound healing. Bilateral 6-mm full-thickness stented wounds were made on the dorsum of Zmpste24 −/− mice. Animals received weekly topical p53 small interfering RNA (siRNA) (n = 25), weekly topical nonsense siRNA (n = 25), daily subcutaneous AMD3100 injections (n = 25), or daily subcutaneous saline injections (n = 25). Wounds were photographically assessed and harvested for reverse transcription polymerase chain reaction, enzyme-linked immunosorbent assay, and immunostaining over 40 days. Circulating EPC levels were measured using fluorescence-activated cell sorting analysis. Local p53 siRNA significantly improved Zmpste24 −/− wound healing (18 ± 2 vs 40 ± 3 days; P ⩽ 0.0001). p53 siRNA significantly increased local provasculogenic factors (hypoxia-inducible factor 1 α, stromal cell-derived factor 1 α, and vascular endothelial growth factor; P ⩽ 0.05) and decreased local proapoptotic factors (p53, PUMA, and Bax; P ⩽ 0.05). Local p53 siRNA also significantly increased the number of circulating EPCs (8 ± 0.2% vs 2.6 ± 0.1%; P ⩽ 0.0001). AMD3100 treatment also significantly improved wound healing (20 ± 2 vs 40 ± 3 days; P ⩽ 0.0001) and increased EPCs mobilization (7.8 ± 0.4% vs 2.6 ± 0.1%; P ⩽ 0.0001). In addition, systemic AMD3100 increased local provasculogenic factors (hypoxia-inducible factor 1 α, stromal cell-derived factor 1 α, and vascular endothelial growth factor; P ⩽ 0.05) and decreased local proapoptotic factors (p53, PUMA, and Bax; P ⩽ 0.05). Both treatments significantly increased the number of blood vessels in the wound bed ( P ⩽ 0.0001). The marked delay in Zmpste24 −/− wound healing is significantly improved by local (p53 siRNA) and systemic (AMD3100) treatments. The resulting decrease in proapoptotic factors and increase in provasculogenic factors in the wound bed as well as the increased level of circulating EPCs appear to reverse age-related wound healing impairment by enhancing wound neovascularization.